VOICING PROSECUTED VICTIMS: A MULTIMODAL ANALYSIS OF PALESTINE LIBERATION MOVEMENT POSTERS - Saputra, Allan Dharma; Kyaw Zeyar Lyn; Rifqi Muhammad Firdaus (CALL, 2025)
This research aims to convey the idea of Palestinian freedom through visual and textual modes. Based on Halliday’s SFL (2004) and Kress & Van Leuween’s (1996) visual grammar framework, this research aims to identify the multimodal features and convey contextual meaning within Palestinian protest posters. Furthermore, through this research, researchers examined how these posters represent the idea of Palestinian freedom through verbal and visual modes. There were five posters from the Palestinian Project Posters website analyzed in this research. The results revealed that Palestinians are depicted as the victimized party both in visual and verbal modes; it also voices the independence values so that people are persuaded to support the Palestinian liberation movement. The research is proposed to unveil the factual condition in Palestine through posters and raise awareness of the Palestinian struggle.